2014
DOI: 10.1097/rli.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-Dose Chest Computed Tomography for Pulmonary Nodule Detection

Abstract: Our study suggests that chest CT for the detection of pulmonary nodules can be performed with third-generation dual-source CT producing high image quality, sensitivity, and diagnostic confidence at a very low effective radiation dose of 0.06 mSv when using a single-energy protocol at 100 kVp with spectral shaping and when using advanced iterative reconstruction techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
96
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(100 citation statements)
references
References 31 publications
4
96
0
Order By: Relevance
“…These ultralow-dose CT acquisitions allow a high sensitivity and diagnostic confidence for the detection of pulmonary nodules [16].…”
Section: Introductionmentioning
confidence: 99%
“…These ultralow-dose CT acquisitions allow a high sensitivity and diagnostic confidence for the detection of pulmonary nodules [16].…”
Section: Introductionmentioning
confidence: 99%
“…Baumueller et al (22) investigated whether HPM for CT enables the diagnostic visualization of lung parenchyma under breathing and found that CT of the lung can be accomplished using HPM at low radiation dose, with maintaining diagnostic image quality even without suspended respiration. Other authors (10,18,19) evaluated HPM for the feasibility in coronary CT angiography and found that CT performed at HPM allows for coronary angiography with high pitch up to 70 bpm. In the above-listed studies, image acquisition was performed ECGgated and did not test HPM for the detection of PE protocols.…”
Section: Discussionmentioning
confidence: 99%
“…It has been pointed out that the diagnostic accuracy of CT could be maintained while reducing the radiation exposure; as a result, it has been claimed about the need of lowering the radiation dose "as low as reasonably achievable" (the ALARA principle) [1] .…”
mentioning
confidence: 99%
“…Nowadays, there are many scientific articles that refer to it, and the field of management of radiation dose has grown as well, significantly [1][2][3] .…”
mentioning
confidence: 99%
See 1 more Smart Citation